2017
DOI: 10.1093/sleep/zsx008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Estrogen and the Decline in Delta Power During Adolescence

Abstract: Study Objectives: During adolescence, there is a precipitous decrease in slow-wave sleep (SWS) and its spectral correlate, delta power, which may reflect cortical reorganization. The temporal association between the decrease in delta power and puberty suggests that sex steroids may initiate these changes. This association has not been previously investigated. Methods: To determine whether estrogen triggers the adolescent decline in delta power, we compared delta power in 14 girls with central precocious pubert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…We observed a positive correlation between the 17-OHP levels and the sleep timing in girls with premature pubarche. These results support the notion that pubertal development is linked to sleep phenotypes, as the elevation of these hormone levels represents the activation of pubarche [26,37]. Recently, Foley et al reported a prospective association between trajectories in pubertal timing and sleep behavior in a large US cohort [31]; those results are in line with our observation that higher 17-OHP levels were associated with a later sleep timing in our study.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a positive correlation between the 17-OHP levels and the sleep timing in girls with premature pubarche. These results support the notion that pubertal development is linked to sleep phenotypes, as the elevation of these hormone levels represents the activation of pubarche [26,37]. Recently, Foley et al reported a prospective association between trajectories in pubertal timing and sleep behavior in a large US cohort [31]; those results are in line with our observation that higher 17-OHP levels were associated with a later sleep timing in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings for delayed bedtimes and wake time for girls with earlier pubic hair development, compared to breast development, may reflect the extrinsic manifestation of androgenic effects associated with declines in SWA. McHill et al (2017), however, reported alternative findings to those of Campbell and colleagues. They reported that neither estrogen nor DHEAS were related to SWA in a small sample of girls with central precocious puberty and age-matched controls.…”
Section: Table 4dmentioning
confidence: 70%
“…The authors hypothesize that the power decline is associated with developmental processes other than physical or sexual maturation. Further evidence for this notion comes from a study investigating delta power in girls with central precocious puberty 81 concluding that increased estrogen does not cause the adolescent decline in delta power.…”
Section: Sleep Eeg Powermentioning
confidence: 99%